Gender differences in metabolic syndrome and its components in southern china using a healthy lifestyle index: a cross-sectional study - Ying Ye; Qiuhong Zhou; Weiwei Dai; Hua Peng; Shi Zhou; Huixia Tian; Lu Shen; Huiwu Han (BMC, 2023)
Abstract Background Lifestyle changes are important for the prevention and management of metabolic syndrome (MetS), but studies that focus on gender differences in the lifestyle risk factors of MetS are limited in China. This research aimed to generate a healthy lifestyle index (HLI) to assess the behavioral risk factors of MetS and its components, and to explore the gender differences in HLI score and other influencing factors of MetS. Methods A convenience sample of 532 outpatients were recruited from a general hospital in Changsha, China. The general information and HLI scores [including physical activity (PA), diet, smoking, alcohol use, and body mass index (BMI)] of the subjects were collected through questionnaires, and each patient's height, weight, waist circumference, and other physical signs were measured. Logistic regression analysis was used to analyze the risk factors of MetS and its components. Results The prevalence of MetS was 33.3% for the whole sample (46.3% in males and 23.3% in females). The risk of MetS increased with age, smoking, unhealthy diet, and BMI in males and with age and BMI in females. Our logistic regression analysis showed that lower HLI (male: OR = 0.838,95%CI = 0.757-0.929; female: OR = 0.752, 95%CI = 0.645-0.876) and older age (male: OR = 2.899, 95%CI = 1.446-5.812; female: OR = 4.430, 95%CI = 1.640-11.969) were independent risk factors of MetS, for both sexes. Conclusion Low levels of HLI and older ages were independent risk factors of MetS in both males and females. The association between aging and MetS risk was stronger in females, while the association between unhealthy lifestyles and MetS risk was stronger in males. Our findings reinforced the expected gender differences in MetS prevalence and its risk factors, which has implications for the future development of gender-specific MetS prevention and intervention programs.